Third Five Year Plan Annual Plan 1963-64 Govt of Andhra Pradesh - Planning Commission (Planning Commission, 1963)
Agricultural Production and Land Development, Training Centres, Consolidation of Holdings, Minor Irrigation, Soil Conservation, Animal Husbandry, Dairying and Milk Supply , Forests, Fisheries, Warehousing and Marketing.
Planning and Panchayati Raj Department, Govt of Andhra Pradesh